الدمج الاجتماعي لذوي الإعاقة الحسية: دراسة فقهية مقاصدية في الأحوال الشخصية - الزنكي، صالح قادر كريم; العرجاني، أمل محمد ظافر (الجامعة الإسلامية العالمية - كلية معارف الوحي والعلوم الإنسانية, 2022)
في ظل تزايد أعداد فئة ذوي الإعاقة، وما حظيت به هذه الفئة من الاهتمام البالغ على الصعيد الطبي والاجتماعي والتربوي من قبل المؤسسات المجتمعية؛ تأتي هذه الدراسة لتعكس اهتمام الشريعة الإسلامية بدمج هؤلاء الأشخاص اجتماعيا وحماية حقوقهم، وتأصيل مبدأ الدمج والمساواة والعدالة بينهم وبين باقي أعضاء المجتمع الواحد، وذلك من خلال دراسة الأحكام الفقهية المتعلقة بذوي الإعاقة الحسية في الأحوال الشخصية؛ بغية استجلاء المقاصد الشرعية من هذه الأحكام، وربطها بالدراسات النفسية والاجتماعية الحديثة من جهة أخرى. وتتمثل إشكالية الدراسة في الحاجة للكشف عن مدى توافق الأحكام الفقهية لذوي الإعاقة مع مقاصد الشريعة. وجمع البحث بين المناهج التالية: الاستقرائي والتحليلي والوصفي والمقارن. وتوصلت الدراسة إلى نتائج، من أهمها: أن الشريعة الإسلامية راعت في أحكامها لذوي الإعاقة الحسية المقاصد الحسية والجسمية، والنفسية، والاجتماعية، كما عنيت بكافة الاختلافات والخصائص التي تميزوا بها عن غيرهم، وأن زواج ذوي الإعاقة يساعد على دمجهم في المجتمع، وتخطي الكثير من الصعوبات التي يواجهونها، والتغلب على هموم الإعاقة. Considering the increase in the number of people with disabilities, and the great attention this group receives from community institutions at the medical, social and educational levels, this research aims to reflect the attention of Islamic Sharīʽah in integrating and protecting the rights of persons with disabilities and establishing the principle of inclusion, equality and justice between them and the rest of the members of the same society by studying the jurisprudential personal status rulings for the people with sensory disabilities. The goal is to clarify the Sharīʽah objectives of these jurisprudential rulings on the one hand and link them to modern psychological and social studies on the other hand. The research problem lies in the need to reveal the compatibility of Sharīʽah rulings for the people with disabilities with the objectives of Sharīʽah. The research combines inductive, analytical, descriptive, and comparative approaches. Among the most important findings of the study is that, in its rulings for the people with sensory disabilities, Islamic Sharīʽah considered the sensory, physical, psychological, and social objectives, as well as all the differences and the characteristics that distinguish them from others. The study also found that marriage helps to integrate people with disabilities into society, overcome many of the difficulties they face, as well as the concerns of disability.
Keywords: ذوي الاحتياجات الخاصة -- أحكام فقهية -- الشريعة الإسلامية -- حكم الزواج